2022
DOI: 10.3390/ani12121497
|View full text |Cite
|
Sign up to set email alerts
|

The Multi-Omics Analysis Revealed Microbiological Regulation of Rabbit Colon with Diarrhea Fed an Antibiotic-Free Diet

Abstract: Diarrhea symptoms appeared after antibiotics were banned from animal feed based on the law of the Chinese government in 2020. The colon and its contents were collected and analyzed from diarrheal and healthy rabbits using three omics analyses. The result of the microbial genomic analysis showed that the abundance of Bacteroidetes and Proteobacteria increased significantly (p-value < 0.01). Transcriptomes analysis showed that differentially expressed genes (DEGs) are abundant in the IL-17 signaling pathway a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In the field conditions in which we nested our study, it was not possible to obtain specimens from all involved suckling rabbits (as the healthy animals could not be sampled); therefore, we opted for a first characterization of the diarrhoea microbiota of the deceased rabbits, sampled from different litters, that may correspond to the final stage of the disease. Despite the observed heterogeneity of the microbiota profiles across samples, also reported within experimental design in other studies (Chen et al., 2022; Wang, Fan, et al., 2022), the most consistent bacterial family and genus across all investigated specimens was Clostridiaceae (24%–57% of the reads of the 16S rRNA gene profiles) and Clostridium (24%–66% of the reads of the same profile), respectively, which might include pathogenic agents or might provide a peculiar signature of the resulted disease status. The genus Clostridium has been reported by the studies of Velasco‐Galilea et al.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In the field conditions in which we nested our study, it was not possible to obtain specimens from all involved suckling rabbits (as the healthy animals could not be sampled); therefore, we opted for a first characterization of the diarrhoea microbiota of the deceased rabbits, sampled from different litters, that may correspond to the final stage of the disease. Despite the observed heterogeneity of the microbiota profiles across samples, also reported within experimental design in other studies (Chen et al., 2022; Wang, Fan, et al., 2022), the most consistent bacterial family and genus across all investigated specimens was Clostridiaceae (24%–57% of the reads of the 16S rRNA gene profiles) and Clostridium (24%–66% of the reads of the same profile), respectively, which might include pathogenic agents or might provide a peculiar signature of the resulted disease status. The genus Clostridium has been reported by the studies of Velasco‐Galilea et al.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, mainly due to the heterogeneity and complexity of these types of disorders in rabbits and, in turn, the complications of the experimental procedures that should be designed, none of the studies that thus far investigated, at the rabbit genome level, DNA markers associated with this pathogenic condition, also attempted to obtain a precise characterization of the putative biological components (e.g., microbiota, viroma) involved as causative factors or derived consequence of the disorder. Only few studies reported information on the microbiota characterization of diarrhoea in rabbits linked to different feeding strategies in specific experimental designs (Chen et al., 2022; Wang, Fan, et al., 2022).…”
Section: Introductionmentioning
confidence: 99%